Delivery Route and the Outcome of Newborn Hearing Screening of Full-Term Neonates Born in a Public Maternal-Infant Hospital in the South of Brazil - Vernier, Luíza Silva; Schneider, Karoline Lemos; Zanini, Claudia; Paniz, Tatiana; Levandowski, Daniela Centenaro (International Archives of Otorhinolaryngology, 2020)
Introduction The newborn hearing screening (NHS) is the most effective strategy for detecting newborns and infants suspected to have hearing loss.Objective To verify possible associations between the route of delivery and the results of the NHS conducted at 3 independent times (24, 36, and 36 hours with a facilitator auricular maneuver [FAM]) in the lives of full-term newborns.Methods A descriptive, observational, prospective study performed with a sample of 462 newborns, with a gestational age ≥ 37 weeks, without risk indicators of hearing loss. The NHS was conducted as a routine element of the facilities, two times: at 24 and 36 hours of life. In the presence of a “failure” in the last test, a new one was immediately performed, following the FAM. Statistic analyses were carried out on the program SPSS version 21.0 (IBM Inc., Armonk, NY, USA).Results Of the 462 newborns assessed, 304 (65.80%) were born by vaginal delivery. There was a statistical significance of “pass” in the NHS for the 24-hour evaluation (p ≤ 0.001 for a vaginal delivery and p = 0.002 for a cesarean delivery), with the prevalence of the “pass” index being higher when the baby's lifespan was greater. A statistically significant difference was not observed when the NHS results were compared by taking into account the babies' routes of delivery and the different times of life.Conclusion These findings show that full-term babies who were born by cesarean did not show more “failure” in the NHS results, contradicting the hypothesis of the study. Furthermore, to reduce the false-negative rates, regardless of the route of delivery, this assessment should be conducted after the first 24 hours of the newborns' life.
Keywords: neonatal screening; hearing; maternal-child health services; public hospital; cesarean section